2017
DOI: 10.1088/1361-6560/62/4/1548
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and compensation of magnetic beam deflection in MR-integrated proton therapy: a method optimized regarding accuracy, versatility and speed

Abstract: The integration of magnetic resonance imaging (MRI) and proton therapy for on-line image-guidance is expected to reduce dose delivery uncertainties during treatment. Yet, the proton beam experiences a Lorentz force induced deflection inside the magnetic field of the MRI scanner, and several methods have been proposed to quantify this effect. We analyze their structural differences and compare results of both analytical and Monte Carlo models. We find that existing analytical models are limited in accuracy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 19 publications
(41 reference statements)
7
64
0
Order By: Relevance
“…The obtained range in Bragg peak displacement of 1–10 mm corresponds well with previous theoretical studies in a homogeneous magnetic field in water . As opposed to a previous study for photons, no systematic differences in absolute dose were found between the film measurements with and without magnetic field, which may be caused by the fact that film dosimeters were oriented perpendicular to the magnetic field in this study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The obtained range in Bragg peak displacement of 1–10 mm corresponds well with previous theoretical studies in a homogeneous magnetic field in water . As opposed to a previous study for photons, no systematic differences in absolute dose were found between the film measurements with and without magnetic field, which may be caused by the fact that film dosimeters were oriented perpendicular to the magnetic field in this study.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, the deflected beam trajectories [see Fig. (a)] did not coincide for different energies, but fanned out energy dependently, as the radius of beam path increases with increasing proton energy . No magnetic field‐induced change in the absolute measured dose was observed.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations